PENGGUNAAN CONTAINER SEBAGAI PENGGANTI TERPAL UNTUK ANGKUT PUPUK PT GRESIK CIPTA SEJAHTERA - Aldi Abdillah, Mohammad Haris; Indro Kirono (AkMen JURNAL ILMIAH, 2023)
Transportation in Indonesia plays a very important role for everyone, because with transportation we can save time and can act as a good service. Many people now use transportation services because they can improve their services, especially in terms of transactions so that people's needs can be met. This research uses descriptive qualitative research methods that can be observed to obtain information from observations to the field. Based on the author's observations, the results of the facts of the existing problems are the existence of customer complaints when the goods arrive at their destination. The complaint in question is damaged or defective goods during the trip or during the delivery process. The condition of the damaged or defective goods is wet fertilizer caused by natural conditions during the trip and leaked / spilled fertilizer from the packaging due to squashed piles. The damage to the goods is because they are still using a trailer truck with an open tailgate, so the proposal in the existing problem is that the shipping process will be eliminated and will be replaced by a container so that the goods are safer and will not take much time during the delivery process.